Virus infections and sudden death in infancy: the role of interferon- - Moscovis, Sophia; Gordon, Ann; Almadani, Osama; Gleeson, Maree; Scott, Rodney J.; Hall, Sharron; Burns, Christine; Blackwell, Caroline (Frontiers in Immunology, 2015)
Respiratory infections have been implicated in Sudden Infant Death Syndrome (SIDS). As interferon- (IFN-) is a major response to virus infection, we examined: 1 ) single nucleotide polymorphism (SNP), IFNG T+874A, in SIDS infants, their parents and ethnic groups with different incidences of SIDS; 2) model systems with a monocytic cell line (THP-1) and human peripheral blood monocytes (PBMC) for effects of levels of IFN- on inflammatory responses to bacterial antigens identified in SIDS; 3) interactions between genetic and environmental factors on IFN- responses. IFNG T+874A genotypes were determined for: SIDS infants from three countries; families who had a SIDS death; populations with high (Indigenous Australian), medium (Caucasian) and low (Bangladeshi) SIDS incidences. The effect of IFN- on cytokine responses to endotoxin was examined in model systems with THP-1 cells and human PBMC to endotoxin. The IFN-γ responses to endotoxin and toxic shock syndrome toxin (TSST-1) were assessed in relation to genotype, gender and reported smoking. There was a marginal association with IFNG T+874A genotype and SIDS (P =0.06). Indigenous Australians had significantly higher proportions of the IFNG T+874A SNP (TT) associated with high responses of IFN-. THP-1 cells showed a dose dependent effect of IFN- on cytokine responses to endotoxin. For PBMC, IFN- enhanced interleukin (IL)-1β, IL-6 and tumor necrosis factor- (TNF-) responses but reduced IL-8 and IL-10. Active smoking had a suppressive effect on baseline levels of IFN-. There was no effect of gender or genotype on IFN- responses to bacterial antigens tested;; however, significant differences were observed between genotypes in relation to smoking. The results indicate virus infections contribute to dysregulation of cytokine responses to bacterial antigens and studies on physiological effects of genetic factors must include controls for recent or concurrent infection and exposure to cigarette smoke.